Causes of mortality in a large population-based cohort of psychiatric patients in Southern Europe. (April 2021) - Girardi, Paolo; Schievano, Elena; Fedeli, Ugo; Braggion, Marco; Nuti, Marco; Amaddeo, Francesco
Abstract: The World Health Organization considers excess morbidity and mortality among people with mental disorders as a high public health priority. This study aims to estimate the mortality risk and causes of death among a large population-based cohort of psychiatric patients. All residents in Veneto (Northeastern Italy) aged between 18 and 84 years with a contact with Community Mental Health Centers in 2008 and a psychiatric diagnosis (n = 54, 350) were followed-up for 10 years. Standardized Mortality Ratios (SMR) and excess mortality were computed, with the general regional population as a reference. Mortality was more than doubled (males SMR = 2.4; females SMR = 2.2) and the relative increase in mortality was much larger in young and middle-aged adults (18–44 and 45–64 years) across all diagnostic groups. The most frequent causes were circulatory diseases (27%) and neoplasms (26%). Although the risk was increased by about tenfold, deaths from suicide were limited to 6% and 4% of all decedents in males and females, respectively. Patients with schizophrenia showed a very high risk for mortality for diabetes and cardiovascular disorders. A large excess was found also for respiratory diseases and a two-fold increase for lung cancer in males and breast cancer in females. Although chronic physical disorders are known to be the main causes of mortality in such patients, they receive far less attention than suicide or accidents. Our results suggest that there is still a need to plan actions to prevent excess mortality and to improve the quality of life of patients with mental disorders.